PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN (Studi pada Toko Anugrah Ban Semarang) - Achmad Nurul Huda, 13.05.51.0148; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2018)
The purpose of this study is to examine the influence of Product Quality, Price and Location on Customer Satisfaction at Semarang Tire Anugrah Store. The dependent variable is Customer Satisfaction. Independent variable are Product Quality, Price and Location. The population in this study was all the customers at Semarang Tire Anugrah Store in 2016. The sample of this study is 100 respondents. This study used purposive sampling method.The analysis used in this reseacrh are multiple linear regression analysis.The results of the testing of hypotheses partial evaluation shows that Product Quality and Price have positive and significant effect to Customer Satisfaction, while Location has positive and insignificant effect to Customer Satisfaction.Keywords: Product Quality, Price, Location, Customer Satisfaction